أثر الغرر في الحكم الفقهي للمشتقات المالية - الزهاميل، مبارك نجم عبدالله; الصلاحين، عبدالمجيد محمود السلام (الجامعة الإسلامية بغزة - عمادة البحث العلمي والدراسات العليا, 2019)
يتناول هذا البحث مفهوم الغرر وتحديد شروط تأثيره في الأحكام الفقهية، ثم الوقوف على المشتقات المالية وأنواعها الرئيسة مبينا مفهوم كل منها وصفاتها وطريقة التعامل بها، ثم عرض الخلاف الفقهي بين المعاصرين في مشروعية التعامل بالمشتقات المالية ثم فحص مدى وجود شروط الغرر المؤثر في الحكم الفقهي لهذه العقود، وكان ختام البحث التنبيه على خطورة مآل التعامل بهذه العقود. ويهدف البحث إلى استجلاء حقيقة المشتقات المالية وخطورتها ومقدار ما شابها من غرر؛ ذلك أن الخلاف الفقهي المعاصر قام في جزء مهم منه على كون المشتقات المالية عقود غرر وأنه بلغ فيها مبلغا يوجب القول بالتحريم وهذا ما ينفيه الفريق المخالف بالقول بأن الغرر فيها يسير ولا يرقى للتأثير في حكم المسألة؛ فكان لابد من تحرير القول في هذا لينبني الحكم الفقهي في المسألة على أسس واضحة. وتوصل البحث إلى القول برجحان القول بتحريم المشتقات المالية بصورتها الحالية اعتمادا على كون المشتقات المالية ترتكز في جوهرها على الغرر وأنه بلغ فيها مبلغ الكثرة وانطبقت عليه شروط التأثير في الحكم.
This research deals with the concept of Gharar and the definition of the conditions of its influence in jurisprudential rulings. In addition to identify the financial derivatives and their main types, indicating the concept of each of them and their characteristics and how to deal with them. Then he presented the jurisprudential dispute existing among the modern in the legitimacy of dealing with financial derivatives and then examined the applicability of the terms of the gharar influential in the jurisprudence of these contracts. The conclusion of the study was the warning about the seriousness of the fate of dealing with these Gharar contracts. The research aims at clarifying the reality of the financial derivatives and their seriousness and the degree to which it contained a Gharar. The contemporary jurisprudential dispute in an important part of it on the fact that financial derivatives contracts Gharar and that it reaches the prohibition. This is what the dissenting team denies by saying that the Gharar is cushy and does not reach to influencing the ruling of the matter. Therefore, it was necessary to liberate the statement in this to build a jurisprudential ruling on the matter on clear grounds. The research concluded to the prohibition of financial derivatives in its present form, which is because that the financial derivatives are essentially based on Gharar and that they reached the amount of the majority and the conditions for influencing the ruling is applied to it.
Keywords: الأحكام الفقهية -- المالية الإسلامية -- الفقه الإسلامي